Septic Olecranon Bursitis caused by Non-tuberculous Mycobacteria, the Mayo Clinic Experience. (4th October 2017) - Jagtiani, Anil; Tande, Aaron; Morrey, Mark; Virk, Abinash
Abstract: Background: Non-tuberculous mycobacteria (NTM) are a rare cause of septic olecranon bursitis (SOB) with few cases reported in the literature. Here we describe clinical outcomes and treatment modalities of 6 patients with SOB due to NTM infections. Methods: This is a retrospective chart review of all adult patients treated at Mayo Clinic between January 2000 and June 2015 with SOB due to NTM. Results: We had 6 patients in our series. Patient characteristics are in Table 1. All patients receiving antibiotics ( n = 5) required ≥12 weeks of therapy. 80% experienced severe side effects requiring either a change in regimen ( n = 3) or discontinuation ( n = 1). The most serious side effect was vestibular toxicity and hearing loss related to tobramycin usage. One patient did not receive antibiotics after surgical debridement and had resolution. Of the 5 patients who required debridement, none experienced complications from surgery. Anconeus muscle flap was required in 1 patient to avoid wound healing issues. All 6 patients achieved resolution of infection at the bursa, but relapse with the same organism at other sites was seen in 2 immunocompromised hosts. Conclusion: SOB due to NTM infections are uncommon and challenging to treat. In our institution, Mycobacterium chelonae was the most frequently implicated organism. Proper microbiologic diagnosis is often delayed. These typically require extensive debridement and prolonged combination antimicrobial therapy. In some instances, more conservative measures may be considered. Although side effects are common, this treatment modality seems to produce clinical improvement. Relapse may be associated with immunosuppression and may occur at different sites. Disclosures: All authors: No reported disclosures.